Implementasi Learning Cycle 5E Dalam Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti Pada Siswa Kelas X SMAN 1 Rendang Karangasem - Ni Ketut Sri Kusuma Wardhani; Ni Wayan Yusi Armini (Jurnal Penelitian Agama Hindu, 2022)
The covid-19 pandemic has significantly influenced the educational field where all instructional processes are shifted to online learning. This study aims to analyze strategy, problems, and implication of the implementation of 5E learning cycle on religious studies and character education of the tenth graders of SMAN 1 Rendang Karangasem during the Covid-19 pandemic. The 5E learning cycle is an application of constructivist approach covering engagement, exploration, explanation, elaboration, and evaluation. This study employs a phenomenological approach where the data is gathered through observation, in-depth interview, literature studies, and documentation studies which are futher analyzed descriptive qualitatively. The study results in showing that the implementation of 5E model begins with the construction of the lesson plan, until the evaluation process. Generally, 5E cycle is conducted online through google classroom, zoom meeting, whatsapps groups, youtube, and educational radio. Further, several problems are found by teachers are mainly because of two factors, they are internal covering biological and psychological aspects, and also external factors including school, family, as well as the infrastructure. The implementation of 5E model has a positive implication in improving students’ ability to master a concept through discussion, motivation of and creativity of the teachers and students, and administer the Tat twam asi principle, confidence, and social care. In short, the implementation of 5E learning cycle is has a positive implication toward students’ ability in learning religious studies and character education.